Soil Fatigue from Induced Seismicity - Merissa L. Zuzulock; Oliver-Denzil S. Taylor; Norbert H. Maerz. (Advances in Civil Engineering)
Induced seismicity and the effects on civil engineering systems are not completely understood and infrequently studied. One specific area that is not well known is soil fatigue which includes factors such as understanding the natural conditions of the subsurface as well as operational parameters under short duration impulse loads. With the increase of geoinduced seismic activity, soil fatigue becomes of greater concern to structures in the vicinity of this seismic load. The foundations of these structures can be affected by impulse loads which can ultimately cause failure. The lack of quantitative data puts the reliability of these civil engineering systems at risk as they are not fully evaluated to determine if they are functioning as they are intended in the environments they are designed to support.